1999
DOI: 10.1034/j.1399-0039.1999.540214.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene frequencies of human platelet antigens in the Tunisian population

Abstract: Gene frequencies for the human platelet antigens HPA-1, -3 and -5 in the Tunisian population were determined by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) on 93 volunteer blood donors (78 were tested for HPA-1, 90 for HPA-3 and 93 for HPA-5). This study shows the highest frequencies of the HPA-1b (0.25) and HPA-5b (0.22) yet recorded. These antigens are considered as markers of a high risk of platelet alloimmunisation in other populations, and for this reason particular atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…healthy unrelated individuals from the center of Tunisia are summarized in Table 1. The distribution of HPA-1, HPA-3, and HPA-5 systems confirms previous Tunisian studies (5)(6) and it is similar to that reported in other Maghrebian populations (Moroccan Berbers and Algerian) (11)(12). Tunisians have the highest frequency for the HPA-1b (0.22) and -5b (0.20) alleles, but the lowest one for HPA-3b allele (0.25).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…healthy unrelated individuals from the center of Tunisia are summarized in Table 1. The distribution of HPA-1, HPA-3, and HPA-5 systems confirms previous Tunisian studies (5)(6) and it is similar to that reported in other Maghrebian populations (Moroccan Berbers and Algerian) (11)(12). Tunisians have the highest frequency for the HPA-1b (0.22) and -5b (0.20) alleles, but the lowest one for HPA-3b allele (0.25).…”
supporting
confidence: 89%
“…Our study confirms again the striking difference in the distribution of the HPA-5 system between Maghrebians and the other populations and the increasing north-south gradient for HPA-5b antigen (6,(13)(14)(15).…”
supporting
confidence: 86%
“…The prevalence of HPA-1b (24%) and HPA-2b (23%) were high among Bahrainis, compared with Africans [3], Asians [5,8], and Europeans [6], which was comparable to rates established for Saudi Arabia [9], Tunisia [10], and North African Berbers [7], suggesting that Arabian Peninsula-North Africa is focus of HPA-1b. The prevalence of HPA-3b (43%) was less selective, as prevalence rates among Bahrainis were comparable to Asians [5,8] and Europeans [6].…”
Section: Discussionmentioning
confidence: 61%
“…The genotype and allele frequencies were estimated by direct counting, and the results were compared with the values published for blood donors and/or healthy individuals worldwide (http://www.ebi.ac.uk/ipd/hpa/freqs_1.html). A 2 test or Fisher's exact test was performed to individually compare the allele frequencies of each HPA polymorphic system between the Amazonas blood donors and the data reported for 38 population groups worldwide (Muniz-Diaz et al, 1993;Santoso et al, 1993;Holensteiner et al, 1995;Kekomaki et al, 1995;Kim et al, 1995;Tanaka et al, 1995;Steffensen et al, 1996;Carlsson et al, 1997;Merieux et al, 1997;Drzewek et al, 1998;Seo et al, 1998;Castro et al, 1999;Korinkova et al, 1999;Mojaat et al, 1999;Rozman et al, 1999;Sellers et al, 1999;Mazzucco et al, 2000;Nogues et al, 2000;Bennett et al, 2002;Ferrer et al, 2002;Boehlen et al, 2003;Jones et al, 2003;Randen et al, 2003;Shih et al, 2003;Halle et al, 2004Halle et al, , 2005Kulkarni et al, 2005;Feng et al, 2006;Pavkovic et al, 2006;De La Vega Elena et al, 2008;Bhatti et al, 2010;Pavic et al, 2010;Tan et al, 2012;Conti et al, 2014). A hierarchical classification of all analysed populations was carried out based on a allele frequencies from five HPA polymorphic systems using Cluster 3·0 and Java Tree View software packages (Eisen Lab, University of California, Berkeley).…”
Section: Discussionmentioning
confidence: 99%